Dinamika Fear of Intimacy pada Individu Dewasa Awal dengan Latar Belakang Orang Tua Bercerai: Sebuah Studi Kasus - Naura Luthfi Nuurmahsa; Fitrania Maghfiroh (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
Intimacy is a fundamental capacity essential for individuals in developing meaningful interpersonal relationships and contributing to psychological well-being and quality of life. Barriers in intimacy development, including fear of intimacy and relational dysfunction, can result in significant psychological consequences such as anxiety and depression, as well as destabilization of intimate relationships with long-term impacts. This study aims to analyze the construct of intimacy, its developmental mechanisms, and its implications for romantic relationship quality and marital stability. Demographic data shows that Indonesia has experienced a substantial increase in divorce rates, reaching 516,544 cases in 2022, indicating significant problems in intimate relationships within society. Through comprehensive analysis of prominent theories such as attachment theory, fear of intimacy theory, and intimacy violation theory, this study identifies protective factors and risk factors that facilitate and hinder intimacy development. Findings indicate that deficits in intimacy capacity correlate with increased risk of divorce, mental health disorders, and relational dysfunction that reduces life satisfaction. The practical implications of this study emphasize the urgency of evidence-based psychological interventions to optimize intimacy development, enhance intimate relationship quality, and promote family stability.